UPAYA ILO-IPEC MELALUI WACAP DALAM MENGELIMINASI DAN MENCEGAH PEKERJA ANAK PADA PERKEBUNAN KAKAO DI GHANA - Vipassani, Prema; Fasisaka, Idin; Parameswari, A.A. Agung Ayu intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT The problem of child labour in West Africa’s cocoa plantations began to draw global attention in the middle of 2000. Ghana is one of the country in West Africa that is getting the spotlight related to the numerous child labourers that work under the hazardous conditions on cocoa plantations. In line with the establishment of Harkin-Engel Protocol as one of the effort to eliminate the worst forms of child labour in cocoa and chocolate industry, the involvement of ILO-IPEC is expected to assist in realizing the protocol’s objective. ILO-IPEC established WACAP, a sub-regional program which conducted in four cocoa producing countries and one rice producing country in West Africa. Ghana is one of the five countries in the scope of WACAP’s implementation. This study aims to describe the efforts of ILO-IPEC through WACAP in eliminating and preventing child labour on cocoa plantations in Ghana. This study assessed by using theory of foreign aid with its two sub-concepts; humanitarian development aid and technical assistance of foreign aid. The locus of this study is from 2002 to 2006. Key Words: child labour, Ghana, ILO-IPEC, cocoa plantations